A nonlinear fatigue damage model: Comparison with experimental damage evolution of S355 (SAE 1020) structural steel and application to offshore jacket structures. (June 2020) - Aeran, Ashish; Acosta, Ruth; Siriwardane, Sudath C.; Starke, Peter; Mikkelsen, Ove; Langen, Ivar; Walther, Frank
Highlights: A nonlinear fatigue damage model based only on S-N curve parameters is proposed. Fatigue damage evolution curves are experimentally derived for S355 structural steel. Material physical behavior is characterized by plastic strain accumulation and changes in electrical resistance and temperature of the microstructure. Experimentally derived damage evolution curves are compared with theoretically predicted damage using proposed model. Application of proposed model is shown to an offshore jacket structure. Abstract: Miner's rule is commonly used in fatigue life estimations and is also recommended by design standards. Recently, a few models have been proposed, to capture loading sequence effects more precisely than Miner's rule. However, practical applications of these models have not been found, due to the requirement for additional material parameters. The authors have recently proposed a nonlinear fatigue damage model, which does not require any additional material parameters, other than the S-N curve. It can be applied by practicing engineers, using partially known S-N curves given in design standards, including the corresponding detail categories. The model has been verified with several materials for both damage evolution curves and fatigue life estimations. Verification of this model for S355 (SAE 1020) structural steel used in offshore structures is desirable for the industry. Experimental techniques, based on characterizing fatigue damage using physical quantities, have also recently been developed by the authors and are used for this verification. Subsequently, damage evolution curves under load increase test and constant amplitude tests are developed by observing the changes in plastic strain amplitude, electrical resistance and temperature. The corresponding fatigue strength curve is developed. This curve is used, together with the proposed damage index, for further verification of the proposed model for S355 (SAE 1020) structural steel. Finally, application of the proposed model is shown for an existing offshore jacket structure, and the results are compared with those of the conventional approach. Hence, the importance and significance of the proposed model is further established.